Incidental CT Findings Suspicious for COVID-19–Associated Pneumonia on Nuclear Medicine Examinations: Recognition and Management Plan. (July 2020) - Tulchinsky, Mark; Fotos, Joseph S.; Slonimsky, Einat
Abstract : Abstract: Some patients undergoing routine SPECT/CT and PET/CT examinations during the COVID-19 pandemic may incidentally reveal findings of COVID-19–associated pneumonia (C-19AP) on localizing CT. It is critical for nuclear medicine physicians to develop diagnostic skills for timely recognition of typical findings of C-19AP on a localizing CT. Furthermore, it is our responsibility to know the optimal practices for safely isolating and managing such patients while protecting the staff, other patients at the facility, family and/or friend accompanying the patients, and the public in general from risky exposure to COVID-19 sources. We offer several steps following an encounter suspicious of C-19AP.